Effect of prior exercise intensity on physiological response and short-term aerobic performance - Caritá, Renato Aparecido Corrêa [UNESP]; Denadai, Benedito Sérgio [UNESP]; Greco, Camila Coelho [UNESP] (FapUNIFESP (SciELO), 2014)
Athletes of different sports have frequently used warm-up exercises as preparation for the training session or competition. Increased metabolism and performance, as well as musculoskeletal injury prevention, are among the reasons that lead coaches to adopt this procedure. The effects of prior exercise have been studied to analyze the limiting factors of physiological adjustments at the beginning of exercise and its effects on subsequent exercise performance. Thus, this article analyzes studies that have investigated the effects of prior exercise on the cardiorespiratory and metabolic responses and short-term aerobic performance. In this context, factors such as prior exercise intensity and duration and recovery period between exercise sessions are discussed, and the possible mechanisms that could explain the effects of prior exercise are presented. The effects of prior exercise on the oxygen uptake (VO2) kinetics do not seem to depend on the prior exercise intensity and recovery period between exercise sessions (i.e., prior and subsequent). However, the effects on exercise tolerance appear to depend on the interaction between the intensity of both exercises and the recovery period between them.
Efeito da intensidade do exercício prévio na resposta fisiológica e na performance aeróbia de curta duração
Keywords: Exercise intensity; Recovery; VO2 kinetics; Warm-up